Self-medication practice among children in Antananarivo, Madagascar - Tsifiregna, Rosa L.; Razafimahatratra, Safidinarindra H.; Raveloharimino, Nirina H.; Rakotomalala, Rivo L. H.; Ravelomanana, Noeline (International Journal of Research in Medical Sciences, 2016)
Background: Self-medication is very common in pediatrics. Little is known about self-medication on children in Antananarivo. The main objective of this study is to evaluate the practice of self-medication on children by their mothers. Methods: A cross sectional descriptive study was done by visiting homes. An interviewer-administered questionnaire was used to gather data on self-medication. Mothers were selected by simple random sampling. Results: Out of the 383 mothers interviewed, 157 have practiced self-medication. The prevalence was 40.99%. The fever was the main symptom treated with paracetamol. On the other hand, the oral rehydration salt has been little used, 6.25% before the consultation. The inappropriate use of antibiotics was found in this study. Drugs were of illegal origin in 40.27% of the cases. The urgency was the main reason for self-medication. Over 80% of mothers knew the risks of self-medication. Thus, the high level of maternal education was among the factors influencing this practice, particularly for children older than 60 months. Conclusions: Information to mothers about the responsible self-medication is necessary.